Iron (II) hexacyanoferrate (II) acid iron (II) sodium material

By adjusting the particle size and surface area of ​​the ferric iron (II) hexacyanol (II) sodium powder and combining with acid decomposition treatment, the problem of sodium ion loss of electrode materials in moisture environment is solved, and its stability and electrochemical properties are improved , extends the battery's cycle life.

CN119137069APending Publication Date: 2024-12-13ALTRIS AB
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380037992.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-10
Filing Date
2023-05-08
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The sodium hexacyanol ferric (II) iron (II) acid sodium electrode material easily leads to sodium ion loss and capacity attenuation in the presence of moisture, affecting its electrochemical performance and cyclic stability.

Method used

By controlling the particle size of the iron (II) hexacyanol (II) iron (II) sodium powder material from 4 μm to 50 μm and the specific surface area of ​​the BET is in the range of 0.1 m2/g to 10 m2/g, the loss of sodium ion is reduced and the moisture stability of the material is improved. Na4Fe(CN)6*10H2O is treated in the range of 50°C to 120°C by acid decomposition method to remove moisture and adjust particle size.

Benefits of technology

It significantly reduces the capacity attenuation of the sodium hexacyanol ferro(II) iron(II) acid in moisture, improves its stability and electrochemical properties, and extends the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119137069A_ABST
    Figure CN119137069A_ABST
Patent Text Reader

Abstract

The present disclosure relates to an iron (II) hexacyanoferrate acid iron (II) sodium material wherein the particles of the iron (II) hexacyanoferrate acid iron (II) sodium material have a particle size D50 value in the range of 4 [mu] m to 50 [mu] m and a BET specific surface area in the range of 0.1 m2 / g to 10 m2 / g.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure generally relates to a sodium iron (II) hexacyanoferrate (II) material, a method for preparing the sodium iron (II) hexacyanoferrate (II) material, an electrode comprising the sodium iron (II) hexacyanoferrate (II) material, and a battery cell of a battery comprising at least one electrode comprising the sodium iron (II) hexacyanoferrate (II) material. Background Art

[0002] Lithium-ion based batteries dominate the market for rechargeable batteries. However, the technology has disadvantages, not least of which is the relative scarcity of lithium resources. While better than previous generations of secondary battery technology, lithium-ion based batteries are not environmentally friendly and are also expensive from a recycling perspective.

[0003] Sodium-ion batteries represent an attractive alternative to lithium-ion batteries and are arguably the most viable way to support renewable energy for the purposes of load leveling and storing excess energy. The performance of sodium-ion batteries depends on the characteristics of the electrode materials. Its cathode material is one of the key factors restricting the application of sodium-ion batteries.

[0004] Prussian blue analog cathode materials stand out as promising cathode materials for use in sodium-ion batteries. Prussian blue analogs have a unique crystal structure with an open three-dimensional framework and large lattice gaps and are able to store sodium ions. The Prussian blue analog of particular interest in this article is sodium iron(II) hexacyanoferrate(II), which has a high Na content and low H2O. Sodium iron(II) hexacyanoferrate(II) has a white color and is often referred to as "Prussian white". Prussian white is a Prussian blue analog with the chemical formula Na2Fe2(CN)6 and a negligible water content (<0.08H2O / fu).

[0005] Drying is particularly important when Prussian White is used as an active cathode material because any water present in the Prussian White structure must be removed in order for the material to fully utilize its capacity in a battery cell. The presence of water can negatively affect the electrochemical potential and cycling stability in a battery cell of a battery that includes Prussian White as a cathode material.

[0006] It has been found that Prussian white materials have variability in stable practical capacity and cycling stability. An important factor that has been identified is the effect of moisture exposure in air on the electrochemical performance of Prussian white materials. It has been found that moisture exposure leads to Na loss in the Prussian white structure and therefore limited practical capacity.

[0007] Therefore, the problem of moisture-driven degradation still exists, and there is thus a need to improve the capacity and moisture stability of Prussian white electrode materials. Summary of the invention

[0008] In view of the above-mentioned and other shortcomings of the prior art, it is an object of the present disclosure to provide improvements related to moisture stability and capacity fade of sodium iron(II)hexacyanoferrate(II) electrode materials.

[0009] This and other objects of the present disclosure are achieved by the sodium iron (II) hexacyanoferrate (II) material according to claim 1. In the following description and drawings, further embodiments are listed in the dependent claims.

[0010] Therefore, the present disclosure relates to a sodium iron (II) hexacyanoferrate (II) powder material. The particles of the sodium iron (II) hexacyanoferrate (II) powder material have a particle size D50 value in the range of 4 μm to 50 μm and a particle size D50 value in the range of 0.1 μm to 1.5 μm. 2 / g to 10m 2 / g in the range of BET specific surface area.

[0011] The particle size distribution was measured by laser diffraction using the Mie theory using a Malvern Mastersizer 3000 instrument with an Areo S standard venturi for powders. The size range was set to 0.1-3500 μm. Prior to analysis, the samples were sieved through a 1 mm sieve.

[0012] The surface area (BET) was measured on an accelerated surface area porosimeter (Micromeritics, ASAP, 2020) with N2 adsorption at 77 K and is expressed in units of area per mass of sample (m 2 / g) indicates.

[0013] "Electrode" should be interpreted broadly herein as an ion source component in various electrochemical devices, such as, but not limited to, batteries, fuel cells, electrochemical devices, and sensors.

[0014] The inventors of the present invention have found that the particle size D50 value is in the range of 4 μm to 50 μm and the BET specific surface area is in the range of 0.1 m 2 / g to 10m 2The sodium iron(II) hexacyanoferrate(II) material in the range of 100 g / g can improve the capacity of the sodium iron(II) hexacyanoferrate(II) material over time by reducing capacity fade (loss of Na), particularly moisture-driven degradation, while maintaining high conductivity. In other words, the loss of sodium in the sodium iron(II) hexacyanoferrate(II) material leads to limited practical capacity and it has been found that the sodium iron(II) hexacyanoferrate(II) material according to the present invention is less prone to Na loss, and thus loses less capacity, when exposed to moisture.

[0015] The particles of the sodium iron (II) hexacyanoferrate (II) powder material may preferably have a particle size D50 value in the range of 7 μm to 50 μm and a particle size D50 value in the range of 0.1 μm to 1.5 μm. 2 / g to 10m 2 The BET specific surface area is in the range of 1000 Å / g. It has been found that the obtained sodium iron(II)hexacyanoferrate(II) material provides improved stability in moisture and thus significantly reduces the capacity decay over time.

[0016] The particle size D50 value of the sodium iron(II) hexacyanoferrate(II) material may be in the range of 10 μm to 30 μm. It has been found that the resulting sodium iron(II) hexacyanoferrate(II) material provides improved stability in moisture and thereby significantly reduces capacity decay over time.

[0017] The particle size D50 value of the sodium iron(II) hexacyanoferrate(II) material may be in the range of 15 μm to 25 μm. It has been found that the resulting sodium iron(II) hexacyanoferrate(II) material provides highly improved stability in moisture and thereby significantly reduces capacity decay over time.

[0018] The BET specific surface area of ​​sodium hexacyanoferrate (II) can be as high as 0.1 m 2 / g to 5m 2 It has been found that the BET specific surface area of ​​sodium hexacyanoferrate (II) material is in the range of 0.1 m 2 / g to 5m 2 The fact that the content of NaFe(II) in the hexacyanoferrate(II) is in the range of 1:1 / g improves the stability of the sodium iron(II) hexacyanoferrate(II) material in moisture. The sodium iron(II) hexacyanoferrate(II) material with a large BET surface area is more easily exposed to moisture, which can cause Na loss and capacity decay over time.

[0019] The BET specific surface area of ​​sodium hexacyanoferrate (II) can be as high as 0.1 m 2 / g to 1m 2It has been found that this significantly improves the moisture stability of the sodium iron(II) hexacyanoferrate(II) material.

[0020] The particle size D10 value of the sodium iron (II) hexacyanoferrate (II) material may be in the range of 1 μm to 20 μm, preferably, the particle size D10 value of the sodium iron (II) hexacyanoferrate (II) material may be in the range of 1 μm to 15 μm. A reduced number of particles having a particle size in the lower range of 1 μm to 20 μm, such as 1 μm to 15 μm, has been seen to improve stability in moisture. Such sodium iron (II) hexacyanoferrate (II) material may additionally have an improved or at least satisfactory conductivity.

[0021] The particle size D90 value of the sodium iron (II) hexacyanoferrate (II) material may be in the range of 10 μm to 600 μm, preferably, the particle size D90 value of the sodium iron (II) hexacyanoferrate (II) material may be in the range of 10 μm to 50 μm. It has been found that such sodium iron (II) hexacyanoferrate (II) material significantly improves the stability of the sodium iron (II) hexacyanoferrate (II) material in moisture.

[0022] The sodium iron(II) hexacyanoferrate(II) material may exhibit a cubic crystal form.

[0023] Preferably, the sodium iron (II) hexacyanoferrate (II) material has the chemical formula Na 2-y Fe[Fe(CN)6]·m H2O, where y<0.2 and 0 <m<3。

[0024] Such Prussian white materials have high sodium content and high theoretical capacity (~170 mAh / g). However, it has been found that the reported stable practical capacity and cycling stability have high variability. An important factor that has been identified is the effect of moisture exposure in air on the electrochemical performance of Prussian white materials.

[0025] The inventors of the present invention have found that the particle size D50 value according to the present disclosure is in the range of 7 μm to 50 μm and the BET specific surface area is in the range of 0.1 m 2 / g to 10m 2 Prussian white materials in the range of 0.1 A / g provide particularly high moisture stability and less Na loss for otherwise moisture-sensitive materials, as demonstrated in the Examples section.

[0026] Furthermore, the present disclosure relates to a method for preparing the sodium iron (II) hexacyanoferrate (II) material according to any one of the preceding claims, the method comprising the following steps;

[0027] - acid decomposition of Na4Fe(CN)6*10H2O in an acid wherein the ratio of H+ to Fe is in the range of 7:1 to 1:1 and the temperature is in the range of 50°C to 120°C during a time period in the range of 0.1 hour to 30 hours to obtain Na 2-y Fe[Fe(CN)6]*mH2O powder, wherein y<0.2 ​​and m is between 0 and 3;

[0028] - separating and drying the powder obtained, said powder having a particle size D50 value in the range of 4 μm to 50 μm and a particle size D50 value in the range of 0.1 μm to 1.5 μm. 2 / g to 10m 2 / g in the range of BET specific surface area.

[0029] The inventors of the present invention have found that the method according to the present disclosure can prepare a nanostructured carbon nanotube having a particle size D50 value in the range of 4 μm to 50 μm and a BET specific surface area in the range of 0.1 m 2 / g to 10m 2 / g range, which improves the stability of the electrode material in moisture and reduces the capacity loss over time. In particular, it has been found that, as disclosed herein, by controlling the amount and time period of the acid during the addition of the acid, the particle size of the material can be advantageously controlled and adjusted to obtain the sodium hexacyanoferrate (II) iron (II) material according to the present disclosure.

[0030] Prior to drying the powder and removing water from the powder, the separation process may be performed by any separation process known in the art.

[0031] The temperature during the acid decomposition step may be in the range of 50°C to 100°C.

[0032] The pressure may be at or near ambient pressure.

[0033] It has been seen that in processes where the temperature during the acid decomposition step is kept in the range of 50°C to 120°C, preferably in the range of 50°C to 100°C and where ambient pressure is maintained, no or very low corrosion of the reactor material is seen.

[0034] The duration of the acid decomposition step may be in the range of 3 h to 24 h, optionally in the range of 3 h to 10 h.

[0035] The duration of the acid decomposition step can be adjusted depending on whether a high yield or a fast process is desired. The inventors of the present invention have found that when the set time is within the range according to the present disclosure, the yield is higher when the process time is extended. A faster process will result in higher material consumption, i.e., a higher amount of material required to achieve the same yield.

[0036] In the step of separating and drying the obtained powder, the powder may have a D50 particle size value in the range of 7 μm to 50 μm.

[0037] The acid in the acid decomposition step may be any one of the following: hydrochloric acid (HCl), citric acid, formic acid, ascorbic acid, acetic acid, sulfuric acid, hydroiodic acid (HI), hydrobromic acid (HBr), nitric acid (HNO3), phosphoric acid (H3PO4). Preferably, the acid in the acid decomposition step is a reducing acid.

[0038] The H+ to Fe ratio may be in the range of 5:1 to 1:1. It has been found that an H+ to Fe ratio in the range of 5:1 to 1:1 provides reduced particle etching, resulting in improved yield and reduced manufacturing cost.

[0039] The H+ to Fe ratio may be in the range of 3:1 to 1:1.

[0040] In another aspect, the present disclosure relates to an electrode comprising a sodium iron(II) hexacyanoferrate(II) material according to the present disclosure.

[0041] In still another aspect, the present disclosure relates to a battery cell of a battery, which comprises at least one electrode according to the present disclosure, and the electrode forms a positive electrode and a sodium source in the battery cell of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Some exemplary embodiments will be described with reference to the drawings, wherein:

[0043] Figure 1 SEM images of sodium iron(II) hexacyanoferrate(II) materials with different particle sizes (D50) according to comparative examples and according to the present disclosure are shown;

[0044] Figure 2 A battery cell of a battery according to the present disclosure is schematically illustrated;

[0045] Figure 3 Two alternative methods for preparing a sodium iron(II) hexacyanoferrate(II) material according to the present disclosure are schematically illustrated; and

[0046] Figure 4 is a graph illustrating the comparison results of a five-day cycle study of four sodium iron(II) hexacyanoferrate(II) materials according to the present disclosure. DETAILED DESCRIPTION

[0047] The sodium iron(II) hexacyanoferrate(II) material according to the present disclosure may have the formula (Na 2-y Fe[Fe(CN)6].mH2O), where y < 0.2 and 0 < m < 3, commonly known as Prussian White.

[0048] The sodium iron (II) hexacyanoferrate (II) material has a particle size D50 value in the range of 4 μm to 50 μm and a particle size D50 value in the range of 0.1 μm. 2 / g to 10m 2 The inventors of the present invention have found that such sodium iron (II) hexacyanoferrate (II) material is more stable in moisture and therefore exhibits reduced capacity decay over time when exposed to moisture. Optionally, the sodium iron (II) hexacyanoferrate (II) material has a particle size D50 value in the range of 7 μm to 50 μm.

[0049] Figure 1 SEM images of sodium iron(II) hexacyanoferrate(II) materials of different particle sizes are illustrated. In image a), the particles have a particle size (D50) of 4.8 μm (D10 of 2 μm, D90 of 275.6 μm), in image b), the particles have a particle size (D50) of 6.3 μm (D10 of 3.8 μm, D90 of 548.3 μm), in image c), the particles have a particle size (D50) of 19.5 μm (D10 of 10.2 μm, D90 of 32.6 μm), and in image d), the particles have a particle size (D50) of 20.5 μm (D10 of 11.8 μm, D90 of 33.3 μm). The BET specific surface area of ​​sample a) and sample b) ranges from 1.97 m 2 / g to>1m 2 / g, and the BET specific surface area of ​​sample c) and sample d) ranges from 0.97 m 2 / g to 0.61m 2 / g, as measured on an accelerated surface area porosimeter (Micromeritics, ASAP, 2020), with N2 adsorption at 77K.

[0050] Figure 2 A schematic principle of a sodium battery comprising an electrode including sodium iron (II) hexacyanoferrate (II) material according to the present disclosure forming a positive electrode and a sodium source 100, using sodium ions 101 as charge carriers. The sodium battery stores energy in chemical bonds of the negative electrode 102. Charging the battery 100 forces the Na + Ions 101 are deintercalated from the positive electrode 103 and migrate to the negative electrode 102. During discharge, the process is reversed. Once the circuit is complete, electrons are transferred back from the negative electrode 102 to the positive electrode 103, and Na + The ions 101 travel back to the positive electrode 103. During discharge of a battery cell, as Figure 1As shown, oxidation occurs at the negative electrode 102, while reduction occurs at the positive electrode 103. The current is determined by the potential difference between the positive electrode 103 and the negative electrode 102 (cell voltage).

[0051] The two electrodes are separated by an electrolyte 104; for example 1 M NaPF6-EC:DEC.

[0052] As used herein, the term "battery" means a device including one or more electrochemical cells.

[0053] In an "electrochemical cell", chemical energy is converted into electricity by reduction and oxidation (redox) reactions at the electrodes.

[0054] Therefore, the positive electrode material includes the chemical formula (Na 2-y Prussian white material of Fe[Fe(CN)6].mH2O), where y<0.2.

[0055] The electrical conductivity is paired with the good rate capability of the cathode material, allowing for rapid charging and discharging.

[0056] As long as the negative electrode material is a material capable of storing / releasing sodium, the negative electrode material is not particularly limited. Examples include metal composite oxides, sodium metal, sodium alloys, silicon, silicon-based alloys, tin-based alloys, bismuth-based alloys, metal oxides, conductive polymers such as polyacetylene, Na-Co-Ni-based materials, hard carbon, etc.

[0057] The battery cell may further include a separator 105 to prevent electrical shorting between the negative and positive electrodes and to provide mechanical stability to the cell. The separator material may be any material that is chemically stable and electrically insulating, such as a polymer film typically made of polypropylene, polyethylene, or a combination of these.

[0058] According to the present invention, the sodium battery Figure 1 The method of the Prussian white material described is shown here Figure 3 and in method 1 comprising the steps of: acid decomposing Na4Fe(CN)6*10H2O in an acid, wherein the H+ to Fe ratio is in the range of 7:1 to 1:1 and the temperature is in the range of 50°C to 120°C during a time period in the range of 0.1 hour to 30 hours, to obtain Na 2-y Fe[Fe(CN)6]*mH2O powder, wherein x<0.2 and m is between 0 and 3; and (B) isolating and drying the obtained powder. In method 2, the difference compared to method 1 is that the mixture of water and Na4Fe(CN)6*10H2O is heated before adding the acid. The powder has a particle size D50 value in the range of 4 μm to 50 μm and a particle size D50 value in the range of 0.1 μm. 2 / g to 10m2 / g in the range of BET specific surface area.

[0059] In method 2, the reaction starts with the acid decomposition of Na4Fe(CN)6*10H2O with an acid, such as HCl, wherein the H+ to Fe ratio is in the range of 7:1 to 1:1. The temperature is maintained in the range of 50°C to 120°C during a time period in the range of 0.1 hours to 30 hours.

[0060] The acid may alternatively be any of the following: citric acid, formic acid, ascorbic acid, acetic acid, sulfuric acid, hydroiodic acid (HI), hydrobromic acid (HBr), nitric acid (HNO3), phosphoric acid (H3PO4). The reaction mixture was then cooled to room temperature (RT) and filtered in air.

[0061] Additional steps may include forming an electrode comprising the Prussian white powder according to the present disclosure. The electrode is prepared by conventional slurry casting, wherein the Prussian white powder prepared according to the present disclosure is mixed with a conductive additive, a binder, and a solvent in a ball mill. The slurry is then deposited on a current collector; the film thickness is controlled by a doctor blade technique. One or more electrodes comprising the Prussian white powder are arranged in a battery cell of a battery and will form one or more high voltage, high capacity, and moisture resistant positive electrodes.

[0062] Devices similar to the electrodes described above, such as fuel cell electrodes, may advantageously include Prussian White powder according to and produced in accordance with the present disclosure.

[0063] Experimental data

[0064] Example 1: Preparation of Prussian blue analog electrode material

[0065] By using the above method and following Figure 3 The steps shown, can be used to synthesize Prussian White to produce the preferred particle size according to the present disclosure.

[0066] Example 2: Comparative study of the cyclic stability of Prussian blue analog powders with different particle sizes and BET specific surface areas

[0067] The resulting powder is mixed with a solvent, a conductive additive and a binder by grinding, such as ball milling, for 1 hour. The solvent may be any type of solvent known to those skilled in the art. The conductive additive may be any type of conductive additive known to those skilled in the art. For example, various types of carbon compounds, such as Super P, C65, C45, carbon black, such as ketjen black, may be used. The binder is not limited to a specific binder. For example, alginate, carboxymethyl cellulose (CMC), styrene-butadiene rubber (SBR), polyvinylidene fluoride (PVdF) may be used. The resulting slurry is then applied to a metal foil and evenly distributed by a scraper. The solvent is removed from the electrode within 30 minutes at 80°C, and transferred to an inert storage container (reference sample) or a storage container with 75% RH for 5 days (exposed sample). All electrodes are then dried at 120°C for 12 hours. The capacity loss presented is the relative difference between the reference sample and the exposed sample.

[0068] In summary, samples according to the present disclosure show a surprising reduction in Na loss and thus improved moisture stability compared to comparative samples with smaller particle size.

Claims

1. A sodium iron (II) hexacyanoferrate (II) material, wherein: The particles of the sodium iron (II) hexacyanoferrate (II) material have a particle size D50 value in the range of 4 μm to 50 μm and a particle size D50 value in the range of 0.1 μm to 1.5 μm. 2 / g to 10m 2 The particle size D50 and the BET specific surface area are determined according to the method disclosed herein.

2. The sodium iron (II) hexacyanoferrate (II) material according to claim 1, wherein: The particle size D50 value is in the range of 7 μm to 50 μm.

3. The sodium iron (II) hexacyanoferrate (II) material according to claim 1, wherein: The particle size D50 value is in the range of 10 μm to 30 μm.

4. The sodium iron (II) hexacyanoferrate (II) material according to claim 1, wherein: The particle size D50 value is in the range of 15 μm to 25 μm.

5. The sodium iron (II) hexacyanoferrate (II) material according to any one of the preceding claims, wherein The BET specific surface area is 0.1 m 2 / g to 5m 2 / g range.

6. The sodium iron (II) hexacyanoferrate (II) material according to any one of claims 1 to 4, wherein The BET specific surface area is 0.1 m 2 / g to 1m 2 / g range.

7. The sodium iron (II) hexacyanoferrate (II) material according to any one of the preceding claims, wherein The particle size D10 value is in the range of 1 μm to 20 μm.

8. The sodium iron (II) hexacyanoferrate (II) material according to any one of claims 1 to 6, wherein The particle size D10 value is in the range of 1 μm to 15 μm.

9. The sodium iron (II) hexacyanoferrate (II) material according to any one of the preceding claims, wherein The particle size D90 value is in the range of 10 μm to 50 μm.

10. The sodium iron (II) hexacyanoferrate (II) material according to any one of the preceding claims, wherein The sodium iron (II) hexacyanoferrate (II) material is a cubic crystal.

11. The sodium iron (II) hexacyanoferrate (II) material according to any one of the preceding claims, wherein: The sodium hexacyanoferrate (II) material has the formula Na 2-y Fe[Fe(CN)6]·m H2O, where y<0.2 and 0 <m<3。 12. A method for preparing the sodium iron (II) hexacyanoferrate (II) material according to any one of the preceding claims, the method comprising the following steps; - acid decomposition of Na4Fe(CN)6*10H2O in an acid wherein the ratio of H+ to Fe is in the range of 7:1 to 1:1 and the temperature is in the range of 50°C to 120°C during a time period in the range of 0.1 hour to 30 hours to obtain Na 2-x Fe[Fe(CN)6]*mH2O powder, wherein x<0.2 and m is between 0 and 3; - separating and drying the powder obtained, said powder having a particle size D50 value in the range of 4 μm to 50 μm and a particle size D50 value in the range of 0.1 μm to 1.5 μm. 2 / g to 10m 2 / g in the range of BET specific surface area.

13. The method for preparing sodium iron (II) hexacyanoferrate (II) material according to claim 12, wherein: The temperature during the acid decomposition step is in the range of 50°C to 100°C.

14. The method for preparing sodium iron (II) hexacyanoferrate (II) material according to claim 12 or 13, wherein: The duration of the acid decomposition step is in the range of 3 h to 24 h, optionally in the range of 3 h to 10 h.

15. The method for preparing sodium iron (II) hexacyanoferrate (II) material according to any one of claims 12 to 14, wherein: The acid in the acid decomposition step may be any one of the following: hydrochloric acid (HCl), citric acid, formic acid, ascorbic acid, acetic acid, sulfuric acid, hydroiodic acid (HI), hydrobromic acid (HBr), nitric acid (HNO3), phosphoric acid (H3PO4).

16. The method for preparing sodium iron (II) hexacyanoferrate (II) material according to any one of claims 12 to 15, wherein: The H+ to Fe ratio is in the range of 5:1 to 1:

1.

17. An electrode comprising the Prussian blue analog material according to any one of claims 1 to 11.

18. A battery cell comprising at least one electrode according to claim 17, said electrode forming a positive electrode and a sodium or potassium source in said battery cell.